Phase I dose-escalation study of stereotactic body radiotherapy (SBRT) for poor surgical candidates with localized renal cell carcinoma. Issue 1 (October 2015) - Ponsky, Lee; Lo, Simon S.; Zhang, Yuxia; Schluchter, Mark; Liu, Yiying; Patel, Ravi; Abouassaly, Robert; Welford, Scott; Gulani, Vikas; Haaga, John Robert; Machtay, Mitchell; Ellis, Rodney J.
Abstract Purpose To evaluate the tolerability of escalating doses of stereotactic body radiotherapy (SBRT) for primary treatment of localized renal cell carcinoma (RCC) in poor surgical candidates. Patients and methods Eligible patients included those with clinically staged radiographic and or pathologically confirmed RCC who had not undergone previous abdominal or pelvic radiotherapy. All patients had comorbid medical conditions which precluded surgery. Median (range) patient age was 77.6 years (range 59–89) years and all patients had Karnofsky Performance Status of ⩾60. Median tumor volume was 57.9 cm3 (range 13.8–174.7 cm3). Dose-limiting toxicity (DLT) was defined as grade 3 or worse gastrointestinal/genitourinary toxicity by Common Terminology Criteria of Adverse Events (version 4). Tumor response was assessed by imaging results using Response Evaluation Criteria In Solid Tumors (RECIST) measurement and percutaneous biopsy. Results A total of 19 patients (13 men and 6 women) were treated on protocol from June 2006 through August 2011. Groups of 3–6 patients received 24, 32, 40, and 48 Gy in 4 fractions. Median (range) follow-up was 13. 7 months (5.9–34.7 months). For possibly treatment-related acute toxicities, one patient developed grade 2 fatigue and one developed grade 4 duodenal ulcer. For possibly treatment-related late toxicities, 2 patients experienced grade 3 renal toxicity (worsening chronic kidney disease), one reported grade 2 urinary incontinence and one developed grade 4 duodenal ulcer. Among the 15 patients with evaluable response, 3 and 12 had partial response and stable disease, respectively, utilizing RECIST criteria. Among the 11 patients who had post-SBRT biopsy, only one (9%) was negative on first biopsy and an additional one (9%) turned negative without further therapy on second biopsy. Conclusions Dose escalation to 48 Gy in 4 fractions has been achieved successfully without dose-limiting toxicities. A planned extension of this phase I trial is currently underway treating patients to 60 Gy in 3 fractions to further evaluate this experimental therapy.